THE EFFECT OF MATERIALİSM ON CONSPICUOUS CONSUMPTION MOTIVATION: EXAMINING THE MEDIATING ROLE OF TRANSFORMATION EXPECTATIONS (Third Sector Social Economic Review, 2022)
In today's world of abundance, consumption does not only mean meeting a physical need. Most of the individuals consume to meet certain expectations. At the same time, consumers' search for commodity-oriented benefits has led to the formation of the relationship between the concepts of materialism and conspicuous consumption in the study. Of course, it is another question mark whether the reasons for consumption can also be related to what the customers think they will add to themselves as a result of shopping. For this reason, it has been enquired whether the expectation of transformation mediates materialism and conspicuous consumption motivation (CCM). When the results are examined, it is understood that there is a significant causality between materialism and conspicuous consumption motivation. At the same time, transformation expectations of consumers may also have a mediating role in this causality. It is thought that this causality is a useful finding in terms of increasing sales during the execution of marketing activities. Moreover, it was noted that the materialist perception focused on Success and Happiness was effective on CCM. Success and Happiness-oriented materialistic perception were found to be effective on CCM while Self, Hedonic, and Efficacy mediate Success's influence on CCM, and only Self mediates Happiness's influence on CCM.
Keywords: Materialism; conspicous consumption motivation; transformation expectations; conspicous consumption; consumer behavior